«Giorgio Angelieri, de Mallo, vicentino» and a new fragment of the library of Bartolomeo Passerotti, now in Kyoto: «Il Petrarca con nuove spositioni» (Venice, 1586) - Marco Daniele Limongelli (TECA)
After an overview of the major stages of Giorgio Angelieri’s publishing activity in Venice and Vicenza, this essay focuses on Petrarch’s works in Italian language published in Angelieri’s printing shop in 1586. We discuss how Petrarch was printed in the second half of the sixteenth century, we trace back to the Lyon’s sources he might look to, and the authors of the accessory materials published along with Canzoniere and Triumphi. Finally, we examine a copy of the book now held in Kyoto, focusing on an ownership inscription by the Bolognese painter Bartolomeo Passerotti.